Solar Fuels: The Rational Design of a Single‐Component Photocatalyst for Gas‐Phase CO2 Reduction Using Both UV and Visible Light (Adv. Sci. 1/2014). (December 2014) - Hoch, Laura B.; Wood, Thomas E.; O'Brien, Paul G.; Liao, Kristine; Reyes, Laura M.; Mims, Charles A.; Ozin, Geoffrey A.
<x xml:space="preserve">Abstract</x> Advances towards the vision of the "solar fuels refinery" of the future are portrayed in the cover art, based on article 1400013 by G. A. Ozin and co‐workers. In the article, the attributes of hydroxide groups and oxygen vacancies are identified for non‐stoichiometric indium oxide photocatalytic nanoparticles in the light‐assisted, gas‐phase conversion of carbon dioxide to carbon monoxide. The ultimate goal of this work is to facilitate an energy transition from today's unsustainable "fossil fuel economy" to a new and sustainable "carbon dioxide economy". The cover was designed by Chenxin Qian <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>